2007
DOI: 10.1007/s11249-007-9211-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing tribological performance of the magnetic tape/guide interface by laser surface texturing

Abstract: The friction coefficient is an important parameter in designing magnetic tape transports. We have introduced a novel approach to reduce the friction coefficient between guides and magnetic tape by laser surface texturing the cylindrical guides. The surface features enhance the formation of an air bearing and hence reduce the friction coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…4b-d. Talke and colleagues [29,30] studied the phenomenon of reducing the friction coefficient between the magnetic tape surface and the guide interface by laser surface texturing (LST) and put a mathematical model that predicts the optimum dimensions for these induced microdimples on the surface that gives the lowest friction coefficient. Current results showed that the existence of such lubricant aggregates or micro-dimples, with some specific geometry and distribution intensity, on the magnetic tape surface resulted in reducing the friction coefficient the same way if they were existed on the guide interface via LST.…”
Section: Surface Topography and Optical Imaging Of The Representativementioning
confidence: 99%
“…4b-d. Talke and colleagues [29,30] studied the phenomenon of reducing the friction coefficient between the magnetic tape surface and the guide interface by laser surface texturing (LST) and put a mathematical model that predicts the optimum dimensions for these induced microdimples on the surface that gives the lowest friction coefficient. Current results showed that the existence of such lubricant aggregates or micro-dimples, with some specific geometry and distribution intensity, on the magnetic tape surface resulted in reducing the friction coefficient the same way if they were existed on the guide interface via LST.…”
Section: Surface Topography and Optical Imaging Of The Representativementioning
confidence: 99%
“…The atmospheric pressure p a was taken to be 0.1 MPa and the viscosity of airl a = 1.81E-5 Pas. The typical standard deviation of asperity summit heights in commercial tape/guide contacts is on the order of r s = 30 nm [7]. This number is the equivalent roughness of the mating tape and guide surfaces, see McCool [18].…”
Section: Optimization Of Dimple Geometrymentioning
confidence: 99%
“…We have used the experimental set-up and procedure outlined in [6] and [7] to measure the friction coefficient between a tape and a guide at tape speeds between 4 and 7 m/s, to make sure the tape operates under full fluid lubrication conditions. Figure 12 shows a comparison between the theoretical predictions and experimental results for a textured guide with a radius R of 15 mm, dimple density S p = 0.15, and dimple aspect ratio e = 0.02.…”
Section: Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…In practice, all these properties of laser light are also used for topographic and microstructural changes, meaning the modification of the surface layers according to a specified pattern [1]. The possibility of efficient and economical creation of well defined regular surface structures may be a successful way to significantly improve the existing or create new properties of numerous materials [2].…”
mentioning
confidence: 99%